DNA Aptamers are Functional Molecular Recognition Sensors in Protic Ionic Liquids. Issue 37 (25th July 2014) - Machado, Isabel; Özalp, Veli Cengiz; Rezabal, Elixabete; Schäfer, Thomas
Abstract The function and structural changes of an AMP molecular aptamer beacon and its molecular recognition capacity for its target, adenosine monophosphate (AMP), was systematically explored in solution with a protic ionic liquid, ethylammonium nitrate (EAN). It could be proven that up to 2 M of EAN in TBS buffer, the AMP molecular aptamer beacon was still capable of recognizing AMP while also maintaining its specificity. The specificity was proven by using the guanosine monophosphate (GMP) as target; GMP is structurally similar to AMP but was not recognized by the aptamer. We also found that in highly concentrated EAN solutions the overall amount of double stranded DNA formed, as well as its respective thermal stability, diminished gradually, but surprisingly the hybridization rate (kh) of single stranded DNA was significantly accelerated in the presence of EAN. The latter may have important implications in DNA technology for the design of biosensing and DNA‐based nanodevices in nonconventional solvents, such as ionic liquids.